2021
DOI: 10.1186/s13005-021-00278-y
|View full text |Cite
|
Sign up to set email alerts
|

The University Münster model surgery system for orthognathic surgery - The digital update

Abstract: Aim The aim of this work is to present a digital methodology of a conventional articulator based planning protocol. Methods The digital counterpart consists of intra-oral scans (3Shape) and a free available 3D mesh software (Meshmixer, Autodesk). The maxillary position in relation to the reference plane used and the arbitrary hinge axis were determined mathematically from landmarks on cephalometric x-rays and frontal photographs. Distances and angl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 13 publications
0
7
0
2
Order By: Relevance
“…It was shown that using the DMMS [ 16 ], the three-dimensional error of the overall process, from preoperative data collection through surgery, to the six-week follow-up, is 0.8 mm ± 0.5 mm and, therefore, below the threshold considered clinically acceptable of two millimeters in translation. The values for pitch (0.9° ± 0.7°), yaw (0.9° ±0.8°), and roll (0.5° ± 0.5°) are also below the clinically accepted four degrees.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It was shown that using the DMMS [ 16 ], the three-dimensional error of the overall process, from preoperative data collection through surgery, to the six-week follow-up, is 0.8 mm ± 0.5 mm and, therefore, below the threshold considered clinically acceptable of two millimeters in translation. The values for pitch (0.9° ± 0.7°), yaw (0.9° ±0.8°), and roll (0.5° ± 0.5°) are also below the clinically accepted four degrees.…”
Section: Discussionmentioning
confidence: 99%
“…The study took place at the University Hospital Münster, Germany. All patients included in this study were virtually planned with the Digital Münster Model Surgery (DMMS) system [ 16 ]. After an interdisciplinary consensus on orthodontic preparation, virtual planning, surgical plan, and intended postoperative occlusion, all patients underwent surgery at the Department of Cranio-Maxillofacial Surgery.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…One feasible approach is the application of software tools to conduct virtual surgery by simulating operative procedures on skeletal models reconstructed from radiological data [ 19 , 20 ]. This allows precise simulation of operative treatment in a time-saving and cost-effective manner, supporting direct visualization of the surgical results, such as bone tunnel drilling and osteotomy [ 21 ]. In clinical practice, virtual surgeries have been adopted for preoperative planning of orthognathic and limb operations.…”
Section: Introductionmentioning
confidence: 99%